2007
DOI: 10.1007/s11294-007-9097-8
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Industry Trade: A Static and Dynamic Panel Data Analysis

Abstract: This study examines the features and determinants of intra-industry trade (IIT), horizontal IIT (HIIT) and vertical IIT (VIIT) between Portugal and the European Union in the period 1996–2002, using a static and a dynamic panel data analysis. The findings indicate that Portuguese VIIT increased significantly during the period in accordance with the values expected for a developed country. The regression results show that there is evidence supporting the explanation of VIIT by Heckscher–Ohlin’s (HO) theory and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
5
17
1
1
Order By: Relevance
“…In general, it is also observable that the three indices produce quite similar results (Table 5). As another general observation, lagged variables are positive and signifi cant in all but one case, similarly to Faustino and Leitão (2007) and Leitão (2011), indicating that past performance plays an important role in present indices.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…In general, it is also observable that the three indices produce quite similar results (Table 5). As another general observation, lagged variables are positive and signifi cant in all but one case, similarly to Faustino and Leitão (2007) and Leitão (2011), indicating that past performance plays an important role in present indices.…”
Section: Resultssupporting
confidence: 65%
“…This hypothesis considers that the most productive sectors have higher levels of product differentiation. Previous studies (Faustino and Leitão, 2007) suggest positive signs for high-quality products and negative for low-quality ones. As the previous section suggests, low-quality agri-food trade prevails in trade among EU-28 Member States; therefore, a negative sign is expected here.…”
Section: H3: Vertical Product Differentiation (Vpd) Encourages (Discomentioning
confidence: 84%
See 1 more Smart Citation
“…In general, it is also observable that the three indices produce quite similar results (Table 4). As another general observation, the lagged variables are positive and significant in all cases, similarly to Faustino and Leitão (2007) and Leitão (2011), indicating that the past performance plays and important role in the present indices.…”
Section: Resultssupporting
confidence: 64%
“…Lee (1989) investigated intra-industry trade for thirteen Pacific countries and found that the product differentiation and FDI were positively related to IIT, while the industrial concentration and IIT were found to be inversely related. Faustino and Leitão (2007) were in search for the determinants of intra-industry trade for Portugal in 1995-2002 and suggested that the physical capital had a negative impact on vertical intra-industry trade, meaning that Portugal exported low-quality products to the European Union. Leitão and Faustino (2008) investigated intraindustry agri-food trade patterns for Portugal in 1995-2003 and found that the economies of scales had a positive, while the industrial concentration had a negative impact on IIT.…”
Section: Empirical Evidencementioning
confidence: 99%